Analysis of #Dirumahaja Hashtags on Instagram Accounts in Persuading People to Stay at Home During the Covid-19 Pandemic in March 2020 - Maharani, Aidina; Nuryana, Arief; Febrianty, Yeni (Indonesian Journal of Advanced Research, 2024)
This study analyzes Instagram content using the hashtag #dirumahaja during the COVID-19 pandemic as part of a campaign to curb virus transmission. It examines how the hashtag conveyed messages to the public. The research focused on Instagram users who posted content with the hashtag in March 2020, using a qualitative descriptive method to explore message dissemination. Findings indicate the AISAS model effectively explains the process, where audiences search for information and share experiences, creating word-of-mouth and virality. This sharing fosters greater public satisfaction and compliance with the campaign’s appeal.